2021
DOI: 10.15381/anales.v82i3.20665
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ability of medical and obstetric students to achieve adequate positive pressure ventilation using basic neonatal resuscitation manikins

Abstract: Introduction. The ability to perform adequate positive pressure ventilation is necessary for neonatal clinical practice. However, there are few studies on the achievements of undergraduate students on this task. It is necessary to assess health science students’ adequate positive pressure ventilation because it is vital at the beginning of their clinical activity. Objective. To evaluate the cognitive and procedural ability related to adequate positive pressure ventilation performed by 6th year medicine student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Teaching neonatal resuscitation improves neonatal resuscitation skills, and teaching neonatal resuscitation to undergraduate health students is part of their academic training in the last years of their studies. Continuous neonatal resuscitation training strengthens the learning of skills designed to help a newborn in its rst minutes of life 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching neonatal resuscitation improves neonatal resuscitation skills, and teaching neonatal resuscitation to undergraduate health students is part of their academic training in the last years of their studies. Continuous neonatal resuscitation training strengthens the learning of skills designed to help a newborn in its rst minutes of life 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Study in Peru about assessing the use of PPV in time of neonatal resuscitation among undergraduate nal year obstetrics and medical students most students had low performance since less than a one fourth of them passed both the theoretical and practical evaluations 10 . This study observed that obstetrics students had better performance on the theoretical knowledge questions but lower performance on the practical assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation